A cell cycle-independent, conditional gene inactivation strategy for differentially tagging wild-type and mutant cells - Nagarkar-Jaiswal, Sonal (eLife, 2017)
Here, we describe a novel method based on intronic MiMIC insertions described in Nagarkar-Jaiswal et al. (2015) to perform conditional gene inactivation in Drosophila. Mosaic analysis in Drosophila cannot be easily performed in post-mitotic cells. We therefore, therefore, developed Flip-Flop, a flippase-dependent in vivo cassette-inversion method that marks wild-type cells with the endogenous EGFP-tagged protein, whereas mutant cells are marked with mCherry upon inversion. We document the ease and usefulness of this strategy in differential tagging of wild-type and mutant cells in mosaics. We use this approach to phenotypically characterize the loss of SNF4Aγ, encoding the γ subunit of the AMP Kinase complex. The Flip-Flop method is efficient and reliable, and permits conditional gene inactivation based on both spatial and temporal cues, in a cell cycle-, and developmental stage-independent fashion, creating a platform for systematic screens of gene function in developing and adult flies with unprecedented detail. DOI: http://dx.doi.org/10.7554/eLife.26420.001